A comparative tale of two methods: how thematic and narrative analyses author the data story differently. Issue 4 (2nd October 2019) - McAllum, Kirstie; Fox, Stephanie; Simpson, Mary; Unson, Christine
ABSTRACT: An interpretive qualitative approach insists on the plural and negotiated nature of the meanings that humans attach to their social realities. Thus, the qualitative researcher must navigate multiple and sometimes conflicting commitments to method, data, oneself, participants, and one's reader. This can lead us to obscure the messiness of data analysis in final research reports and to downplay how methodological choices can make our participants 'say things.' In this article, we compare two interpretive methods, thematic and narrative analysis, including their shared epistemological and ontological premises, and offer a pedagogical demonstration of their application to the same data excerpt. However, our broader goal is to use the divergent results to critically examine how our choice of analytic method in interpretive research influences how we (researcher + method) 'author' data stories. Ultimately, researcher reflexivity must go beyond acknowledging how one's position may influence the data analysis or the participant.